Longitudinal studies: An essential component for complex psychiatric disorders. (January 2016) - McInnis, Melvin G.; Greden, John F.
Highlights: Longitudinal studies of psychiatric disorders form the current basis for nosology. The clinical course of bipolar disorder is a major feature of the phenotype. Nearly half of the observation time in bipolar disorder shows symptoms of disease. Major depression is often comorbid with other medical and psychiatric illness. Combined treatment with medicine and therapy is most effective for depression. Abstract: Most psychiatric syndromes are chronic and lifetime in course. Kraepelin's seminal work pointed out a century ago that longitudinal/lifetime assessments were powerful aids in differentiating dementia praecox from manic-depressive disorder. Despite this, clinical research investigations in psychiatry have historically emphasized short-term and cross-sectional approaches. This review of an array of longitudinal studies supports that they are arguably an essential component of psychiatric investigations, but that they must be coupled with other approaches. The use of standardized, validated, repeated assessments in a disease over the course of time must be incorporated with pathophysiology investigations to identify underlying mechanisms, biomarker studies, comparative effectiveness clinical trials to identify the best treatments for different causes, and translational strategies to provide the right treatments to the right patients at the right time. Strategies for incorporating longitudinal assessments into newer diagnostic proposals, such as the Research Domain Criteria (RDoC), are discussed.